Fabrication of hydrogels with elasticity changed by alkaline phosphatase for stem cell culture. (1st January 2016) - Toda, Hiroyuki; Yamamoto, Masaya; Uyama, Hiroshi; Tabata, Yasuhiko
Graphical abstract: Abstract: The objective of this study is to design hydrogels whose elasticity can be changed by alkaline phosphatase (ALP) in cell culture and evaluate the effect of hydrogel elasticity on an osteogenic gene expression of cells. Hydrogels were prepared by the radical polymerization of acrylamide (AAm), N, N ′-methylenebisacrylamide (BIS), and Phosmer™M containing phosphate groups (PE-PAAm hydrogels). The storage modulus of PE-PAAm hydrogels prepared was changed by the preparation conditions. When human mesenchymal stem cells (hMSC) were cultured on the ALP-responsive PE-PAAm hydrogels in the presence or absence of ALP, the morphology of hMSC was observed and one of the osteogenic differentiation markers, Runx2, was evaluated. By ALP addition into the culture medium, the morphology of hMSC was changed into an elongated shape without cell damage. ALP addition modified the level of Runx2 gene expression, which was influenced by the modulus of PE-PAAm hydrogels. It is concluded that the elasticity change of hydrogel substrates in cell culture had an influence on the Runx2 gene expression of hMSC. Statement of Significance: Stem cells sense the surface elasticity of culture substrates, and their differentiation fate is biologically modified by substrate properties. Most of experiments have been performed in static conditions during cell culture, while the in vivo microenvironment is dynamically changed. In this study, we established to design an enzyme-responsive hydrogel whose elasticity can be changed by alkaline phosphatase (ALP) in cell culture to mimic in vivo conditions. As a result, the cells were deformed and the gene expression level of an osteogenic maker, Runx2, was modified by ALP treatment. This is the novel report describing to demonstrate that the dynamic alteration of hydrogel substrate elasticity could modulate the osteoblastic gene expression of human MSC in vitro.